EF Bart’s Disease with Coinheritance of Gγ-XmnI and Aγ-Globin Polymorphisms: A Case of Nontransfusion-Dependant Thalassemia - Kane M. Laks; Cara Hirner; Barbara Gruner; Jared Coberly; Katsiaryna Laziuk; Bindu Kanathezhath Sathi (Case Reports in Hematology)
EF Bart’s disease is a rare form of nontransfusion-dependant thalassemia (NTDT) due to the coinheritance of homozygous hemoglobin E (βE/βE) genotype with hemoglobin H disease. These individuals are routinely found to have thalassemia intermedia with moderate anemia, increased hemoglobin Bart’s and hemoglobin F on electrophoresis. The contribution of hemoglobin F-inducing polymorphisms in this disease has not been described previously. Here, we describe the hematological profile in a young child with coinheritance of Gγ-XmnI and Aγ-globin gene polymorphisms in EF Bart’s disease. Interestingly, in this rare form of NTDT, normal HbF and elevated HbA2 were noted.